Meningkatkan Hasil Belajar Matematika Materi Bangun Ruang Menggunakan Model Pembelajaran Kooperatif Tipe STAD Siswa Kelas VI SDS 2 Kristen - Esni Esni (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This research was conducted to determine mathematics learning through cooperative learning model type STAD can improve student learning outcomes in solving problems on the material wake-up space. The subjects of this Classroom Action Research were students of Class VI SDS 2 Kristen, with a total of 11 students, consisting of 8 male students and 3 female students. Geographically, SDS 2 Kristen is located in an urban village. With parental educational background ± 48% elementary school, ± 24% junior high school, and ± 28% high school. While the economic background of parents is ± 45% farm laborers, ± 50% farmers and the rest are traders. This condition causes the learning motivation of the sixth-grade Christian SDS 2 students to be a little low. The results of temporary observations are only 47% of students can complete the work of building space well through the use of the STAD (Student Team Achievement Division) learning model. The researcher is a teacher at SDS 2 Kristen collaborating with other classroom teachers at SDS 2 Kristen.Based on the results of the study that the STAD type cooperative learning model in mathematics learning in the Building Space material can improve student learning outcomes.Cycle I after learning mathematics with the STAD type cooperative model. The average score of student learning outcomes is 64.00. In cycle II the average score of student learning outcomes on the subject of Building Space is 79.20.